Entomotoxic potential of hydroalcoholic extract of Eragrostis plana Nees in experimental model of Nauphoeta cinerea Olivier (Acta Scientiarum. Biological Sciences, 2023)
The objective of this study was to evaluate the entomotoxic activity of the hydroalcoholic extract of Eragrostis plana Nees in an experimental model of cockroaches (Nauphoeta cinerea Olivier), for a possible bioinsecticide. For this purpose, aerial parts of E. plana were grounded to obtain the hydroalcoholic extract (EACA), after preparing the concentrations of (0.5; 2.5; 5.0; 12.5; 25.0; 50.0 100.0 Î¼g g-1 per animal) a saline solution was used to control the treatment. To determine the receptors and pathways involved in responses to EACA doses of E. plana, a treatment with the drug octopamine and its inhibitor phentolamine were prepared. The effect of EACA on behavioral activities (grooming) and on cardiac activity were tested. All data were expressed as mean ± standard deviation, being analyzed by the two-way ANOVA test, followed by the Tukey test, considered significant when p